2022
DOI: 10.1002/advs.202202453
|View full text |Cite
|
Sign up to set email alerts
|

Protein Binding Nanoparticles as an Integrated Platform for Cancer Diagnosis and Treatment

Abstract: Smart nanomaterials constitute a new approach toward safer and more effective combined anti‐cancer immunotherapy. In this study, polydopamine‐multiprotein conjugates (DmPCs) that can be used for targeted delivery of multiple proteins to cells, realize imaging and combine the advantages of multiple treatment methods (photothermal therapy, chemodynamic therapy, and immunotherapy) can be synthesized and characterized. Proteins, as biological agents, are frequently used in this context, given their low toxicity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Polydopamine-loaded iron (Fe/PDA) was obtained as described previously. [12] As shown in Figure 1a,d, Fe/PDA had an average diameter of 110 nm and a high degree of uniformity. GOx was then transplanted onto the surface of Fe/PDA via acylation.…”
Section: Preparation and Characterization Of Npsmentioning
confidence: 84%
See 2 more Smart Citations
“…Polydopamine-loaded iron (Fe/PDA) was obtained as described previously. [12] As shown in Figure 1a,d, Fe/PDA had an average diameter of 110 nm and a high degree of uniformity. GOx was then transplanted onto the surface of Fe/PDA via acylation.…”
Section: Preparation and Characterization Of Npsmentioning
confidence: 84%
“…GOx was then transplanted onto the surface of Fe/PDA via acylation. [12] To optimize the water stability and dispersibility of Fe/PDA@GOx, HA was coated on the surface by electrostatic adsorption. The resulting Fe/PDA@GOx and Fe/PDA@GOx@HA had average diameters of 150 nm (Figure 1b,e) and 170 nm (Figure 1c,f), respectively.…”
Section: Preparation and Characterization Of Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polydopamine (PDA) is a kind of biomimetic material of mussel, which can be obtained by self-polymerization of dopamine in weak alkaline environment. 31 PDA has many excellent properties, such as simple preparation, good biocompatibility, and excellent photothermal properties. 32 The structure of PDA contains a large amount of catechol and primary and secondary amines, so that PDA can be adsorbed on the surface of most substances to form a layer of polyamine film.…”
Section: Introductionmentioning
confidence: 99%
“…10 Although some studies combining imaging and multiple treatment methods have been reported, there are still problems, such as complicated syntheses, low bioavailability or poor permeability, and none is in the clinical application stage. [11][12][13][14] Thus, a small organic drug molecule with near-infrared (NIR) fluorescence imaging ability has significance for promoting the clinical applications of integrated diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%